Onecut Factors and Pou2f2 Regulate the Distribution of V2 Interneurons in the Mouse Developing Spinal Cord - Harris, Audrey; Masgutova, Gauhar; Collin, Amandine; Toch, Mathilde; Hidalgo-Figueroa, Maria; Jacob, Benvenuto; Corcoran, Lynn M.; Francius, Cédric; Clotman, Frédéric (Frontiers in Cellular Neuroscience, 2019)
Acquisition of proper neuronal identity and position is critical for the formation of neural circuits. In the embryonic spinal cord, cardinal populations of interneurons diversify into specialized subsets and migrate to defined locations within the spinal parenchyma. However, the factors that control interneuron diversification and migration remain poorly characterized. Here, we show that the Onecut transcription factors are necessary for proper diversification and distribution of the V2 interneurons in the developing spinal cord. Furthermore, we uncover that these proteins restrict and moderate the expression of spinal isoforms of Pou2f2, a transcription factor known to regulate B-cell differentiation. By gain- or loss-of-function experiments, we show that Pou2f2 contribute to regulate the position of V2 populations in the developing spinal cord. Thus, we uncovered a genetic pathway that regulates the diversification and the distribution of V2 interneurons during embryonic development.